First Principles Calculations on the Electronic, Elastic, Structural, and Magnetic Properties of Co2RuGe and Co2NiGe FH Alloys - Sattar, Muhammad Usman; Murtaza, G.; Ali Shah, Syed Farhan; Rafiq, Ammara; Younas, Muhammad (Journal of Materials and Physical Sciences, 2023)
Utilizing first principles, the structural, elastic, magnetic, and electronic properties of Co2YGe FH (Full-Heusler) alloys where Y is Ni, Ru have been examined. The partial and total densities of states, as well as electronic band structures, have been calculated. The Co2YGe alloys half metallic-nature is confirmed by the computed band structures, which show that the valence and conduction bands in the up spin channel overlap at the Fermi-level while here is a band-gap between them in the down spin channel. These compounds have ½ (half) metallic properties, as seen by the TDOS and PDOS. According to mechanical characteristics, the alloys Co2NiGe and Co2RuGe are highly stiff and they respectively are ductile and brittle. By their magnetic characteristics this is demonstrated that compound have Para magnetism property as their net magnetic moment is not zero. According to the results, these alloys could be a contender for spintronic devices.